Project Report on C Code Verification Automation Tools - BHIMSEN K JOSHI (2004)
INTERNAL GUIDE: SHANTAKUMARPATIL, MVJCE EXTERNAL GUIDE: VIJAY KANVI, LKAR SOFTWARE ENGINEER, IT CORPORATES
Keywords: C Code Verification Automation Tools